Gambaran Profil Lipid Anggota Aktif Klub Prolanis Maleosan Kota Tomohon - Vera Diane Tombokan (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Monitoring of health status including lipid profiles, is one of Prolanis' activities routinely, regular monitoring of lipid profiles will be very helpful in knowing the health status of an individual. The purpose of this study was to obtain an overview of the lipid profile active members Maleosan Club, Tomohon City. The type of this research used was descriptive. The sampling technique used was purposive sampling with a total sample of 43 active members of the Prolanis Club Maleosan, Tomohon City. The data collected is the result of medical records of active members of the Maleosan Club in Tomohon City during 2019. The results of statistical tests using the descriptive statistics showed that the active members of the Prolanis Maleosan Club in Tomohon City aged 60-79 years were 38 people (88.4%), woman were 31 people (72.1%), total cholesterol wanted and slightly high, 32 people ( 74.4%), Optimal LDL, close to optimal and slightly high amounted to 31 people (72.1%.), normal HDL amounted to 35 people (81.4%), and optimal and slightly high triglycerides amounted to 38 people (88.3%). Activeness in following Prolanis club activities needs to be maintained and improved to achieve an optimal quality of life.